Molecular mechanism of crisaborole combined with erythromycin against methicillin-resistant Staphylococcus aureus in vivo and in vitro - Zou, Yinuo; Yu, Lei; Xue, Jinjing; Fang, Tianqi; Sun, Liping; Wang, Jianfeng; Cui, Minhe; Zhang, Peng; Zhou, Yonglin (Frontiers in Microbiology, 2025)
The widespread presence of methicillin-resistant Staphylococcus aureus (MRSA) severely threatens convenient therapeutic options in the postantibiotic era. The use of combinations of existing drugs at this stage may be a viable strategy for dealing with complex drug-resistant MRSA infections. An checkerboard MIC (Minimum Inhibitory Concentration) assay, growth curve assay, bactericidal test and scanning electron microscope (SEM) assays were performed to determine whether crisaborole (AN2728), a PDE4 inhibitor for treating atopic dermatitis (AD), produced bactericidal effect with different antibiotics. Here, we identified (AN2728) produced a significant synergistic bactericidal effect with erythromycin, cefuroxime and rifampicin against different bacterial strains of Staphylococcus aureus (S. aureus), especially MRSA (FIC < 0.5) (p < 0.05). Transcriptome analysis, bacterial biofilm assay and several kit assays revealed that AN2728 could also simultaneously affect the membrane and transporter capacity of MRSA. Moreover, in a mouse skin infection model of MRSA, the combination of AN2728 and erythromycin showed remarkable treatment benefits, as shown by significantly reduced bacterial loading (p < 0.05), pathological lesions of the skin and an obvious anti-inflammatory effect (p < 0.05). To our knowledge, this study is the first to establish that AN2728 can cooperate with antibiotics such as erythromycin to completely kill MRSA and that AN2728 can be used to extend the usage life of different antibiotics to address the inevitability of severe MRSA infection.